2002
DOI: 10.1046/j.1472-765x.2002.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping and RAPD profiles of Salmonella enterica isolates from Mauritius

Abstract: Aims: The genus Salmonella is a common agent of gastroenteritis in Mauritius, generating more cases of the disease during summer than during winter. The aims of this study were to assess the genetic diversity of isolates of Salmonella enterica by RAPD fingerprinting, and to establish the relationship between human and chicken isolates. Methods: Twenty‐six isolates were obtained from hospital laboratories and commercial poultry producers locally. Results: The RAPD profiles, biochemical and serological analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…RAPD markers were used because they have the potential to detect polymorphism in the entire genome as compared to other techniques [23]. RAPD markers have been used for strain differentiation [24], identification and other genetic analysis for several bacterial genera during the last two decades [23,[25][26][27][28]. Taken together, the present study was undertaken to assess the potentiality of RAPD as a marker for analysing the diversity of R. solanacearum collected from some fields of some selected locations.…”
mentioning
confidence: 99%
“…RAPD markers were used because they have the potential to detect polymorphism in the entire genome as compared to other techniques [23]. RAPD markers have been used for strain differentiation [24], identification and other genetic analysis for several bacterial genera during the last two decades [23,[25][26][27][28]. Taken together, the present study was undertaken to assess the potentiality of RAPD as a marker for analysing the diversity of R. solanacearum collected from some fields of some selected locations.…”
mentioning
confidence: 99%
“…PCR-based fingerprinting using RAPD has been used widely for genome identification, and the RAPD technique using up to six primers has been reported to be a good tool for molecular typing, permitting the execution of public health measures necessary to control infection (Chansiripornchai et al, 2000;De Cesare et al, 2001;Khoodoo et al, 2002;Quintaes et al, 2002). During this study, we found that the best amplification conditions for RAPD-PCR were an annealing temperature of 35ºC with 3 µL primer.…”
Section: Resultsmentioning
confidence: 80%
“…RAPD was used as it has the potential to detect polymorphism in the entire genome as compared to other techniques (Hilton and Penn 1998). RAPD markers have been used for strain differentiation (Mesquita et al 1998), identification and other genetic analysis for several bacterial genera (Akopyanz et al 1992;Mazurier et al 1992;Parent et al 1996;Hilton and Penn 1998;Khoodoo et al 2002).…”
Section: Discussionmentioning
confidence: 99%